The Application Of Speed Reading To Increase Reading Comprehension For The First Grade Students Of Mas Al- Amin North Labuhanbatu - Syifa Fadhilah (Yayasan Insan Cipta Medan, 2023)
This research observed the application of speed reading to increase reading comprehension for the first grade students of SMA Antartika Sidoarjo. This research was undertaken in class X-1 comprising 40 students involving a writer and an observer. The research was conducted through a classroom action research (CAR). The result showed that speed reading technique could be used to increase the students reading skills. The use of speed reading technique could be effective if it was supported by the ability of the teacher on planning learning in the classroom involving activities proportionally in the instructional process. Carrying a classroom climate was conducive by adequating learning facilities and infrastructure. The successful application of speed reading technique could be seen from the presence of students’ positive response and their active participation in each learning activities.